Colloidal Photonic Crystal‐Enhanced Fluorescence of Gold Nanoclusters: A Highly Sensitive Solid‐state Fluorescent Probe for Creatinine. Issue 2 (29th December 2022) - Thomas, Meghana Mary; Babu, Aswathy; Chandran, Parvathy R; S, Silpa T; Pillai, Saju
Abstract: Gold nanoclusters (AuNCs) are an intensely pursued class of fluorophores with excellent biocompatibility, high water solubility, and ease of further conjugation. However, their low quantum yield limits their applications, such as ultra‐sensitive chemical or molecular sensing. To address this problem, various strategies have been adopted for augmenting their fluorescence intensity. Herein, we report a facile and scalable approach for the fluorescence enhancement of bovine serum albumin (BSA) capped AuNCs (BSA‐AuNCs) using periodic, close‐packed polystyrene colloidal photonic crystals (CPCs). The slow photon effect at the bandgap edges is utilized for the increased light‐matter interactions and thereby enhancing the fluorescence intensity of the BSA‐AuNCs. Compared to the planar polystyrene control sample, the CPC film yielded a 14‐fold enhancement in fluorescence intensity. Further, we demonstrated the as‐prepared BSA‐AuNCs‐CPC as a solid‐state platform for the highly sensitive and selective fluorescence turn‐off detection of creatinine at nanomolar level. Abstract : A facile approach based on polystyrene‐based three‐dimensional colloidal photonic crystal as an efficient platform for augmenting the fluorescence intensity of BSA‐capped AuNCs is reported. A 14‐fold enhancement in fluorescence intensity was achieved and this was employed for the selective and sensitive detection of creatinine.